Partisipasi Anggaran, Kepuasan Kerja, dan Kinerja Manajerial: Studi Pada Bisnis Keluarga Pempek di Kota Palembang - Andison Andison; Yvone Augustine (Faculty of Economic and Business, 2017)
Budgetary Participation, Job's Satisfaction, and Managerial Performance: Study at Pempek's Business Family in Palembang CityAs a business institution, every business unit must have profit orientation including the business family. This study is going to investigate the managerial performance in pempek business family. The purpose of this study to determine: first, the effect of budgetary participation on managerial performance. Second, mediating effect job satisfaction in the relationship budgetary participation on managerial performance. The analysis technique that used in this study is path analysis. The results showed that budgetary participation has no effect on managerial performance, while the job satisfaction is mediating effect on managerial performance at family business Pempek in Palembang.DOI: 10.15408/ess.v7i1.4720